Comparison of Low Back Pain Recovery and Persistence: A Descriptive Study of Characteristics at Pain Onset. (July 2016) - Starkweather, Angela R.; Lyon, Debra E.; Kinser, Patricia; Heineman, Amy; Sturgill, Jamie L.; Deng, Xiaoyan; Siangphoe, Umaporn; Elswick, R. K.; Greenspan, Joel; Dorsey, Susan G.
Background: Persistent low back pain is a significant problem worldwide. Early identification and treatment of individuals at high risk for persistent low back pain have been suggested as strategies to decrease the rate of disability associated with this condition. Purpose: To examine and compare demographic, pain-related, psychological, and somatosensory characteristics in a cohort of participants with acute low back pain who later went on to experience persistent low back pain or whose pain resolved within the first 6 weeks after initial onset. Methods: A descriptive study was conducted among men and women 18–50 years of age who had an acute episode of low back pain. Study questionnaires were administered to collect demographic information and measures of pain, coping, reactivity, mood, work history and satisfaction, and disability. A standardized protocol of quantitative sensory testing was performed on each participant at the painful area of their low back and at a remote site on their arm. Results: The sample consisted of 48 participants, of whom 19 went on to develop persistent low back pain and 29 resolved. Compared to the resolved group, the persistent low back pain group was significantly older and had a lower level of educational attainment, a higher body mass index, and higher mean "least" pain score on the Brief Pain Inventory–Short Form. Significantly higher thermal detection thresholds at the painful and remote sites as well as signs of central sensitivity differentiated the persistent pain group from the resolved group during the acute stage of low back pain.